User Experience dan Usability Testing Bank Maluku Malut Mobile Banking Menggunakan User Experience Questionnaire dan System Usability Scale - Nataldo Noya; Nina Setiyawati (LPPM STIKOM Tunas Bangsa, 2024)
Mobile banking is another major technological advancement in the banking sector. Due to the widespread use of smartphones, banks have developed mobile applications that enable customers to carry out various financial transactions through their mobile devices. For this reason, good user experience (UX) and usability are very necessary because they have a direct impact on the user experience and the success of the application. Good user experience and usability of an application not only increases user satisfaction, but also influences user confidence in the product or service and its long-term success. This research aims to evaluate the level of UX and usability of the Maluku Malut mobile banking application by using the User Experience Questionnaire (UEQ) and System Usability Scale (SUS) to determine user perceptions of the UX and usability of the Maluku Malut mobile banking application. The measurement results provide a positive impression in almost all aspects, and have acceptable usability for users.